The Effects and Mechanism of Yinqiao Powder on Upper Respiratory Tract Infection - Liu, Li-Song; Lei, Na; Lin, Qing; Wang, Wei-Li; Yan, Han-Wen; Duan, Xiao-Hua (International Journal of Biotechnology for Wellness Industries, 2015)
Pharmacology of Chinese materia medica use modern scientific methods based on the theory of Traditional Chinese Medicine (TCM) to study the interactional regulations between the body and Chinese materia medica. It aims to explain the mechanism and the scientific basis of the effects of traditional Chinese medicine. Research team has found that Yinqiao Powder has good effect on the mouse model of upper respiratory trace mucosal immunity dysfunction induced by cold stimulation with bacteria and viruses. Therefore, the function of Yinqiao Powder in the prevention and in the treatment of upper respiratory tract infection (AURI) cannot be explained only by antibacterial and antiviral properties. The effects of Yinqiao Powder on AURI may be mediated by the improvement of the function of upper respiratory mucosal immune system.